1995
DOI: 10.1152/ajpheart.1995.268.3.h1053
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II inhibition of L-type Ca2+ current in sinoatrial node cells of rabbits

Abstract: The actions of angiotensin II (ANG II) were examined in the spontaneously active cells isolated from the rabbit sinoatrial node, using the nystatin-permeabilized, whole cell, patch-clamp method. At 30 nM, ANG II significantly lowered the spontaneous firing rate of the action potentials from 212 +/- 21 to 172 +/- 32 beats/min, with a concomitant reduction in the action potential amplitude. The voltage-clamp experiments showed that ANG II inhibited the L-type Ca2+ current (ICa) with a dissociation constant (Kd) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…Moreover, the dialysis into the cell of PD 123,319 (10 Ϫ6 mmol/L), an angiotensin type 2 (AT 2 ) receptor blocking agent, performed in 6 myocytes did not alter the effect of the peptide on I Ca (nϭ6; PϾ0.05; not shown). Because there is evidence that Ang II when added to the bath reduces I Ca in cardiac pacemaker cells, 15 it is reasonable to think that the peptide dialyzed into the cytosol might leave the cell and interact with AT 1 receptors located at the surface cell membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the dialysis into the cell of PD 123,319 (10 Ϫ6 mmol/L), an angiotensin type 2 (AT 2 ) receptor blocking agent, performed in 6 myocytes did not alter the effect of the peptide on I Ca (nϭ6; PϾ0.05; not shown). Because there is evidence that Ang II when added to the bath reduces I Ca in cardiac pacemaker cells, 15 it is reasonable to think that the peptide dialyzed into the cytosol might leave the cell and interact with AT 1 receptors located at the surface cell membrane.…”
Section: Resultsmentioning
confidence: 99%
“…13 Previous observations by Allen et al 14 indicated that Ang II when added to the bath increases the L-type calcium current in cultured neonatal heart cells. Recently, Habuchi et al 15 demonstrated that in the sinoatrial node of the rabbit, Ang II reduces I Ca when added to the extracellular fluid.…”
mentioning
confidence: 99%
“…In another study, Ang II induced spontaneous action potentials in partially depolarized preparations of rabbit atria and increased the rate of diastolic depolarization and spontaneous discharge in human atrial tissues (22). In rabbit sinoatrial node cells, Ang II depolarized the RMPs accompanied by a reduction of the action potential amplitude and a negative chronotropic effect (23). In isolated rabbit ventricular myocytes, Morita et al (24) reported that Ang II decreased the APD after 3 min of application, but prolonged the APD after application for 7 min.…”
Section: Mechanism Of Ang Ii-induced Shortening Of the Atrial Action mentioning
confidence: 92%
“…In spontaneously beating heart preparations, ANG II induced negative chronotropism, which became significant at a concentration of 10 -9 ·mol·l -1 . Nanomolar concentrations of ANG II had a negative chronotropic effect in pacemaker cells of rabbit through modulation of the L-type Ca 2+ current (Habuchi et al, 1995). In electrically paced preparations, ANG II at 10 -8 ·mol · l -1 and 10 -7 ·mol·l -1 caused a significant decrease in VS and WS, indicating a direct negative modulation of mechanical performance.…”
Section: Effects Of Ang II On Basal Cardiac Performancementioning
confidence: 93%